Association between Stress and Hypertension among Adults More Than 30 Years: A Case-Control Study - Sandip Bhelkar; Sonal Despande; Sharad Mankar; Prabhakar Hiwarkar (Medsci Publications, 2018)
Background: Stress has long been listed as a potential and impor- tant cause of hypertension. Acute stress can induce transient ele- vation of blood pressure. But it is unclear whether stress results in sustained elevation of blood pressure and hypertension. Aims & Objectives: To study the association between hyperten- sion and stress among hypertensive subjects aged above 30 years using perceived stress scale. Material & Methods: Newly diagnosed hypertensive patients aged 30 and above with age and gender matched controls were selected. Sociodemographic variables, history of addiction and physical activity were recorded using predesigned proforma. BMI was calculated for assessing obesity. Stress was assessed using Perceived Stress Scale. Blood pressure was recorded as per JNC- VII criteria. Results: High stress was significantly associated with hyperten- sion. Overweight and obesity, and lack of adequate physical activ- ity were found to be significantly associated with hypertension. These factors were analysed in logistic regression model. Stress was found to be an independent risk factor for hypertension. Conclusion: High stress is significantly associated with hyperten- sion and is an independent risk factor for hypertension.